A significant review on different cooling agent during rapid cooling process of low carbon steel - M. A., Mohd Saaroni; Norazlianie, Sazali; M. F., Ghazali (2020)
Low carbon steel has been chosen as the engineering material in this project to research the comparison of the effects of cooling agent during rapid cooling process and to develop a mechanical data of low carbon steel after the heat treatment. This material has been chosen because it is mostly used for deep drawing of motor car bodies, motor cycle parts and other domestic applications where it need to involve the desired mechanical properties processes. Rapid cooling process or quenching is common process to obtain certain material properties such as increasing strength and hardness. This process is widely used in industry to obtain required properties of any application.